1997
DOI: 10.1073/pnas.94.19.10397
|View full text |Cite
|
Sign up to set email alerts
|

Fos B mutant mice: Loss of chronic cocaine induction of Fos-related proteins and heightened sensitivity to cocaine’s psychomotor and rewarding effects

Abstract: Chronic exposure to cocaine leads to prominent, long-lasting changes in behavior that characterize a state of addiction. The striatum, including the nucleus accumbens and caudoputamen, is an important substrate for these actions. We previously have shown that long-lasting Fos-related proteins of 35-37 kDa are induced in the striatum by chronic cocaine administration. In the present study, the identity and functional role of these Fos-related proteins were examined using fosB mutant mice. The striatum of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
190
1
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 262 publications
(203 citation statements)
references
References 31 publications
11
190
1
1
Order By: Relevance
“…This ceiling effect could in part be because of the dose used and the fact that COC was administered in the animal home cages. It has been shown that COC at a dose of 10-20 mg/kg dose would be inclined to give rise to stereotyped behaviors (Hiroi et al, 1997). Such behaviors, like sniffing and rearing, would have been difficult to detect with the telemetric system used.…”
Section: Coc-induced Ngfi-b Expression In Tg Micementioning
confidence: 99%
“…This ceiling effect could in part be because of the dose used and the fact that COC was administered in the animal home cages. It has been shown that COC at a dose of 10-20 mg/kg dose would be inclined to give rise to stereotyped behaviors (Hiroi et al, 1997). Such behaviors, like sniffing and rearing, would have been difficult to detect with the telemetric system used.…”
Section: Coc-induced Ngfi-b Expression In Tg Micementioning
confidence: 99%
“…18 In humans, the functional activity of the NAc is associated with the subjective effects of cocaine 6 and with craving for cocaine. 7,8,19 In addition to the cocaine-induced NAc plasticity, studies in rodent models indicate persistent or even permanent biochemical alterations in regions associated with the mesolimbic dopamine pathway including upregulation of the cyclic AMP (cAMP) pathway, [20][21][22][23][24][25][26] activator protein 1 family members [27][28][29][30][31][32] as well as glutamate, dopamine, gaminobutyric acid (GABA) and opiate receptors, growth factors, cytoskeletal elements and cell metabolism. [33][34][35][36][37][38][39][40][41] Genomic analyses in human post-mortem tissue of cocaine overdose (COD) victims have confirmed the findings of studies employing rodent models and have revealed novel mechanisms of drug-induced neuronal and non-neuronal dysregulation in human post-mortem brain tissue.…”
Section: Introductionmentioning
confidence: 99%
“…DFosB encodes for stable transcription factors of 33, 35 and 37 kDa (Chen et al, 1997), which are induced in a region-specific manner in the brain as a response to various chronic perturbations (Hope et al, 1994;Doucet et al, 1996;Hiroi et al, 1997). In a rat model of Parkinson's disease, DFosB-like immunoreactivity provides a cellular marker to map neuronal systems that become activated by chronic, dyskinesiogenic treatment with L-DOPA .…”
Section: Introductionmentioning
confidence: 99%